Rehydration characteristics of dehydrated West African pepper (Piper guineense) leaves - Okpala, Laura C (Food Sci Nutr, 2014)
The rehydration characteristics of dehydrated West African pepper leaves were investigated at hydration temperatures of 28, 60, 70, and 80°C. Four treatments were given to the leaves: blanched and sun dried, unblanched and sun dried, blanched and shade dried, and unblanched and shade dried. The hydration process of the dehydrated leaves was adequately described by the Peleg's equation. As the hydration temperature increased from 28 to 70°C, there was a significant decrease in the Peleg's constant K(1), while for most of the leaves the Peleg's constant K(2) varied with temperature. Rehydration ratio values ranged from 3.75 in blanched shade dried leaves to 4.26 in unblanched sun dried leaves with the unblanched leaves generally exhibiting higher ratios than the blanched leaves.